Radio-frequency method for investigation of quantum properties of superconducting structures. - Il’ichev, E.; Smirnov, A.Yu.; Grajcar, M.; Izmalkov, A.; Born, D.; Oukhanski, N.; Wagner, Th.; Krech, W.; Meyer, H.-G.; Zagoskin, A. (Фізико-технічний інститут низьких температур ім. Б.І. Вєркіна НАН України, 2004)
We implement the impedance measurement technique (IMT) for characterization of interferometer-
type superconducting qubits. In the framework of this method, the interferometer loop is inductively
coupled to a high-quality tank circuit. We show that the IMT is a powerful tool to study
a response of externally controlled two-level system to different types of excitations. Conclusive
information about qubits is obtained from the read-out of the tank properties.